Historical Study of the Results of the American War on Iraq between (2003- 2020) - Alfahham, Muayad Baqer Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The Iraq Aggression is the antagonism that not once terminated. That’s accurate exactly, in (U.S)throngs are tranquil in Iraq certain (17 years)later the American attack, with metaphorically, in allegations terminated Iraq — why the (U. S) attacked, what exited erroneous, whether altered consequences were conceivable— endure to impact (U.S) extraneous guiding principle besides inland legislations to this diurnal. The Iraq Aggression takes a noteworthy dispute in each one constitutional choice then it initiated in 2003. It consumes cast a sleuth done each one of successive confab of whether, everyplace, with in what way the U. States would apply potency. It devours sore deliberations completed whether America ought recommit that one to a striving inter - continual or wrench earlier since the Middle East besides feasibly the wider world. It devours ghostly American direction.